Visions of Beirut : The Urban Life of Media Infrastructure - El-Hibri, Hatim, 1980- (Book collections on Project MUSE., 2021)
"Hatim El-Hibri explores how the creation and circulation of images has shaped the urban spaces and cultural imaginaries of Beirut, showing how images can be used to consolidate or destabilize regimes of power."--